TESTING IN THE SOCIAL STUDIES. - Anderson, Howard R. (Education, 1938)
This article discusses certain important functions of testing the learning ability of social studies students from the viewpoint of social studies teachers in the U.S. Social studies teachers usually teach five classes with an average of thirty students in each class. Under these circumstances the adjustment of instruction to individual needs is very difficult. Such adjustment is difficult unless the teacher quickly acquires an insight into the strengths and weaknesses of his students. Certain desirable lines of adjustment become clear if one considers the differences characterizing a typical group of sixty ninth grade students. This study compares the pupils in this group on the basis of their scores on the Terman Group Intelligence Test. For placement purposes a general achievement type of test in social studies is very useful.